Nutritional Status and Clinical Outcome in Postterm Neonates Undergoing Surgery for Congenital Heart Disease*. Issue 5 (June 2015) - Mitting, Rebecca; Marino, Luise; Macrae, Duncan; Shastri, Nitin; Meyer, Rosan; Pathan, Nazima
Abstract : Objective: Poor growth is a common complication in infants with congenital heart disease. There has been much focus on low birth weight as having increased risk of adverse outcomes following neonatal heart surgery. In this study, we examined whether preoperative nutritional status, measured by admission weight-for-age z score, was associated with postoperative clinical outcome. Design: Retrospective case series. Setting: Pediatric Cardiac ICU at the Royal Brompton Hospital. Patients: Neonates undergoing surgery for congenital heart disease. Those undergoing ductus arteriosus ligation alone were excluded. Children with coexisting noncardiac morbidity were excluded. Outcome variables included prevalence of postoperative complications (including sepsis, delayed chest closure, renal impairment, and necrotizing enterocolitis), duration of ventilation, intensive care stay, postoperative mortality, and mortality at 1 year after surgery. Interventions: None. Analysis of patient data only. Measurements and Main Results: Two hundred forty-eight neonates fulfilled the entry criteria. Median (interquartile range) age was 7 days (2–15 d), median (interquartile range) weight was 3.3 kg (2.91–3.6 kg), and median weight-for-age z score was –0.77 (–1.44 to 0.01). Twenty-eight children (11%) had a weight-for-age z score of less than –2. There was no evidence that children with lower weight-for-age z score had less severe surgery as measured by the Risk Adjustment for Congenital Heart Surgery 1 score. In multivariable regression analysis, the weight-for-age z at admission had strong correlation with the number of days free of respiratory support (invasive and noninvasive ventilation) at 28 days ( p < 0.0001) and with all-cause mortality at 1 year ( p = 0.001). Conclusions: Poor nutritional status as measured by weight-for-age z is associated with adverse short- and long-term outcomes in neonates undergoing surgery for congenital heart disease.